Empowerment and Partnership Programs in Healthy Community Movements Through Integrated Development Posts (IDP) of Non-Communicable Disease (NCD) - Tantut Susanto; Erwin Nur Rif'ah; Irawan Fajar Kusuma; Suyani Indriastuti (LP2M Universitas Jember, 2022)
Optimizing the role of the community in the Healthy Community Movement (HCM) through the facilitation of health cadres at the Integrated Development Post (IDP) of non-communicable diseases (NCDs) to become an effective solution of health promotion program using empowerment and partnerships in the community as a form of active participation in health. The purpose of this community service was to increase community empowerment and partnerships in overcoming NCDs problems through HCM to reduce hypertension in Glagahwero Village, Panti District, Jember Regency. The activities were carried out for 3 months (August - November 2020) in the form of education and health counseling about HCM and hypertension, anti-hypertensive exercise, hypertension diet, empowerment of family cooking in the management of family salt consumption, and IDP of NCDs. The fostered village service activities involved 70 target groups. The results were found that the community was able to do HCM to control blood pressure by doing anti-hypertensive exercises once a week, mothers were able to prepare a low-salt menu in their families, and IDP of NCDs activities were carried out once a month. The further impact was a decrease in mean systolic blood pressure (130.5 ± 22.5 mmHg Vs. 122.3 ± 18.3 mmHg; p = <0.001) and diastolic (81.83 ± 10.4 mmHg Vs. 79.4 ± 9.1 mmHg; p = 0.015), decreased body weight (60.6 ± 12.1 kg Vs. 59.7 ± 12 kg; p <0.001), and decreased abdominal circumference (88.5 ± 14.2 cm Vs 82.7 ± 14.1 cm; p <0.001) after 3 months of community service development. Thus, it can be concluded that the partnership and empowerment of the community in HCM is able to prevent PTM, so it is suggested that IDP of NCDs activities need to be carried out in a sustainable manner in the community.